Processing snakehead fish as a high-protein modern healthy food product in the snakehead fish farmers' group - A. Maya Rupa Anjeli; Riski Dwi Prameswari; Anisaul Hasanah (Universitas Muhammadiyah Malang, 2024)
This activity is a response to the impact of the Covid-19 pandemic, which has led to a high unemployment rate in Gresik since March 2020. Several industries have conducted layoffs, affecting 2,300 employees and leading to an increase in poverty levels. The Community-Based Empowerment Program in Tenggor Balongpanggang Village was initiated as a solution. This village is rich in snakehead fish resources but requires human resource development in its distribution. Through training, the villagers will learn how to enhance the added value of snakehead fish, turning it into a high-protein modern healthy food product that can be marketed, providing economic benefits for both the commodity and UD Sumber Rejeki Lestari. The main objectives of this activity are to introduce UD Sumber Rejeki Lestari as the source of raw materials for snakehead fish, provide information about business opportunities through partnerships, create business opportunities for the community through partnerships, and improve the community's skills in processing snakehead fish.